2019
DOI: 10.1101/668335
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Humanization of yeast genes with multiple human orthologs reveals principles of functional divergence between paralogs

Abstract: 1Despite over a billion years of evolutionary divergence, several thousand human genes possess 2 clearly identifiable orthologs in yeast, and many have undergone lineage-specific duplications in 3 one or both lineages. The ortholog conjecture postulates that orthologous genes between species 4 retain ancestral functions despite divergence over vast timescales, but duplicated genes will be free 5 to diverge in function. However, the retention of ancestral functions among co-orthologs between 6 species and withi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 47 publications
(78 reference statements)
2
16
0
Order By: Relevance
“…[49]) and for some types of genes [1], the higher similarity of orthologs in some newer datasets was accompanied by either no change in functional similarity over time [2,5] or the increase in functional similarity over time [43]. As a decrease in structural [41,37] and functional [23,35,34,4,9,32] similarity with divergence is a widely expected and observed pattern for both paralogs and orthologs, the patterns of evolution in these studies are indeed baffling. Further examination of several of these studies has uncovered problems with the analyses such that there is either no longer support for the ortholog conjecture [15] or that there was no statistical support for the ortholog conjecture in the first place, as in the case of human-mouse comparisons in Ref.…”
Section: Introductionmentioning
confidence: 68%
“…[49]) and for some types of genes [1], the higher similarity of orthologs in some newer datasets was accompanied by either no change in functional similarity over time [2,5] or the increase in functional similarity over time [43]. As a decrease in structural [41,37] and functional [23,35,34,4,9,32] similarity with divergence is a widely expected and observed pattern for both paralogs and orthologs, the patterns of evolution in these studies are indeed baffling. Further examination of several of these studies has uncovered problems with the analyses such that there is either no longer support for the ortholog conjecture [15] or that there was no statistical support for the ortholog conjecture in the first place, as in the case of human-mouse comparisons in Ref.…”
Section: Introductionmentioning
confidence: 68%
“…Cross-species gene swaps provide an opportunity to directly test the functional divergence of orthologous genes even over large evolutionary timescales. While Saccharomyces cerevisiae (Baker’s yeast) and Homo sapiens (humans) diverged from their opisthokont ancestor nearly a billion years ago, both species still share thousands of orthologous genes and high-throughput humanization assays in yeast have found that many human genes are capable of substituting for their yeast orthologs with rates up to 47%, depending on strains and assays 57, 911 . Most of these complementation tests until recently were performed in the absence of gene family expansions and revealed many humanizable systems, including the proteasome, and sterol and heme biosynthesis pathways 59, 11 .…”
Section: Discussionmentioning
confidence: 99%
“…While Saccharomyces cerevisiae (Baker’s yeast) and Homo sapiens (humans) diverged from their opisthokont ancestor nearly a billion years ago, both species still share thousands of orthologous genes and high-throughput humanization assays in yeast have found that many human genes are capable of substituting for their yeast orthologs with rates up to 47%, depending on strains and assays 57, 911 . Most of these complementation tests until recently were performed in the absence of gene family expansions and revealed many humanizable systems, including the proteasome, and sterol and heme biosynthesis pathways 59, 11 . In this study, we sought to better understand the functional equivalence of human and yeast orthologs that play key structural roles in the eukaryotic cytoskeleton, particularly focusing on how gene family expansions in cytoskeletal lineages might have diversified in function across their respective gene families.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations